Economic dualism and labour re-allocation in South Africa, 1917-1970 - Hindson, Douglas Carlisle (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 1975)
The central concern of this study is to analyse how the pattern of development in South Africa has influenced the long term growth of productive employment in the economy. The approach adopted is to appply a model of economic dualism to the South African case. Chapter 1, p. 1.
Keywords: Labor policy -- South Africa -- History -- 20th century; Labor laws and legislation -- South Africa; Labor economics -- South Africa